Isolation of reactor-borne neptunium using ion specific extraction chromatography resins and detection by gamma spectroscopy - Rosenberg, Brett L., author; Steinhauser, Georg, advisor; Johnson, Thomas, committee member; Miller, Charles, committee member (Colorado State University. Libraries, 2014)
Although actinides are the most informative elements with respect to the nature of a nuclear accident, plutonium analysis is complicated by the background created by fallout from nuclear explosions. Therefore, 239Np, a short-lived actinide (T1/2 = 2.4 d) that emits several gamma rays, is proposed herein as a suitable proxy. The most prominent photopeaks from 239Np are at 106 keV, 228 keV, and 278 keV. However, the 106 keV and 228 keV photopeaks of 239Np are also characteristic of 129mTe and 132Te, volatile fission products with half-lives of 33.6 days and 3.2 days, respectively. Although not as pronounced, there is also some spectral interference of the 278 keV peak with the 284 keV peak of 131I. The aim of this study was to screen the available ion specific resins provided by Eichrom Technologies, LLC, for the highest possible recovery and isolation of trace amounts of 239Np from samples with large amounts of fission and activation products such as radiocesium, 131I, and 129mTe. The investigated environmental media for these separations were aqueous solutions (simulating rainwater) and soil. Aqueous solutions containing 239Np and volatile radionuclides were filtered through UTEVA, Actinide, RE, and TRU Eichrom® resin columns to ascertain the most effective means of isolating 239Np from other fission and activation products for detection. This was followed up with isolation of 239Np from a soil matrix. The resins most effective for eluting 239Np from aqueous solution were UTEVA and RE (90±13% and 50±7%, respectively, calculated via the 278 keV peak yield). Isolation of 239Np from soil using these columns was found achievable only by washing out the entire 239Np-loaded stationary phase from the resin columns with acetone. This suggests that soil components can contribute to the formation of organometallic complexes within the resin matrix that enhance the retention of tetravalent neptunium. Analysis of the tellurium, cesium, and iodine content in eluates, washing solutions, and resins was conducted. Substantial fission product exclusion from eluates was found for TRU resins, RE resins, and UTEVA resins, although exclusion varied by the eluent used. In conclusion, the RE and UTEVA resins with HNO3 as a loading solution and eluent provide the best recovery of 239Np from rainwater samples while suppressing volatile radionuclides. Separation of neptunium from volatile radionuclides in soil requires further investigation, although we have demonstrated that the techniques used herein are effective at extracting neptunium from a soil matrix for detection by gamma spectroscopy.